Molecular Distributions of Soluble Oxidation Products from Coals Characterized by Mass Spectrometers - Xing Fan; Fei Wang (International Journal of Analytical Chemistry)
Oxidation of three coals with rank from lignite to anthracite in NaOCl aqueous solution was investigated in this study. The oxidation products were characterized by using gas chromatography/mass spectrometry and direct analysis in real-time mass spectrometry. The results showed that most of organic compounds in coals were converted into water-soluble species under mild conditions, even the anthracite. Benzene polycarboxylic acids (BPCAs) and chloro-substituted alkanoic acids (CSAAs) were major products from the reactions. The products from lower rank coals consist of considerable CSAAs and most products from high rank coals are BPCAs. As coal rank increases, the yield of BPCAs with more carboxylic groups increases.